Study on interlocking concrete block pavement made with shredded tyre - Siti Zumayah Saad (School of Environmental Engineering, University Malaysia Perlis, 2012)
Increasing production of vehicles also cause a lot of increasing a waste of rubber tire. Discarded rubber tires can cause environmental pollution problems around the world. The study was conducted to find alternatives to overcome the problem of rubber tyre disposal increased in recent times. Waste rubber tyre is a substance that can be used in industry because of itslightweight, flexible and absorb energy. This study were conduct to compare compressive strength and density between concrete block pavement made with shredded tires with control sample paving block and to produce green interlocking paving block made with shredded tire. Rubber tyre collected from landfill has been cut into a small pieces to replace the sand in accordance with a predetermine percentage. Then the rubber tyre is mixed with cement, sand, foam and water to produce a lightweight concrete. This study shows the results of an experimen about the normal concrete sample is made with the concrete addition of shredded tyre in 7 days and 28 days. Tyre waste has been used again in this study to replace the fine aggregate with the volume of rubber tires in a different percentage of rubber content. Five different volumes of rubber tires were used there is 5%,10%,15%,20%, and 25%. Results of experiments are compared with the ordinary concrete blocks which is have the same characteristics and concrete blocks obtained from the factory. The results obtained show that the concrete with the addition of rubber tires of 15% have a higher compression strength than other rubber additional percentage.